The pastoral in vulnerable girls' enviroments. (2020)
The present reflection seeks to know what role the pastoral plays in environments of girls who have been the object of abuse, maltreatment or abandonment, finding as central elements the culture, the spiritual dimension, and a pastoral incarnation as a condition for a Church mediating salvation. This problem is approached from the pastoral work, the realization of pedagogical playful workshops oriented to the promotion of the full personal fulfillment from the desire of Christ in each one of the girls is a primordial objective. It is equally important to accompany the population and their families in an interdisciplinary way in the process of comprehensive training for girls through different strategies.